Asymptomatic hepatosplenomegaly in chronic myeloid leukemia. Issue 10 (18th September 2018) - Imataki, Osamu; Uemura, Makiko
Abstract: A 39-year-old male diagnosed as chronic myeloid leukemia, had no abdominal symptoms. However, his physical examination revealed apparent abdominal fullness. His liver and spleen were palpable. His abdominal CT revealed that a narrow space to pass intestinal digestive contents. Asymptomatic hepatosplenomegaly is somewhat typical in these chronic type hematological diseases.